Supporting sustainable development (ESG) through the EFQM 2020 business excellence model - Głuszek, Ewa; Martusewicz, Joanna (Journal of Management and Financial Sciences, 2025)
The concept of sustainable development includes a set of activities that constitute a holistic vision of development, which is a balance of environmental, social and economic dimensions. Business excellence models are tools that can support organizations in implementing the principles of sustainable development and serve to evaluate this process. However, these models are not always characterized by an integral approach, i.e. taking into account all three aspects mentioned. The aim of the article is to analyze the EFQM (2020) model in terms of its reflection of ESG sustainable development factors included in the European reporting standards (ESRS) and to propose possible modifications to the model. These changes should make it easier for organizations to orient themselves towards implementing sustainable practices in their operations.